2005
DOI: 10.1080/02724980443000151
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss and Perceptual Effort: Downstream Effects on Older Adults’ Memory for Speech

Abstract: A group of older adults with good hearing and a group with mild-to-moderate hearing loss were tested for recall of the final three words heard in a running memory task. Near perfect recall of the final words of the three-word sets by both good- and poor-hearing participants allowed the inference that all three words had been correctly identified. Nevertheless, the poor-hearing group recalled significantly fewer of the nonfinal words than did the better hearing group. This was true even though both groups were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
381
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(421 citation statements)
references
References 41 publications
34
381
1
5
Order By: Relevance
“…Nevertheless, higher-order processing operations depend on the extraction of syllables from the acoustical signal based on the analysis of the acoustic features that make up each utterance. Indeed, evidence from older subjects suggests that syllable discrimination skills correlate directly with verbal memory performance when cognitive factors are controlled [63][64]. This finding supports the notion that perceptual success of HA users comes at the cost of the extra effort that is needed for analyzing phonemes and might otherwise be available for analyzing sentence content.…”
Section: Effect Of Training On Sentence Processingsupporting
confidence: 74%
“…Nevertheless, higher-order processing operations depend on the extraction of syllables from the acoustical signal based on the analysis of the acoustic features that make up each utterance. Indeed, evidence from older subjects suggests that syllable discrimination skills correlate directly with verbal memory performance when cognitive factors are controlled [63][64]. This finding supports the notion that perceptual success of HA users comes at the cost of the extra effort that is needed for analyzing phonemes and might otherwise be available for analyzing sentence content.…”
Section: Effect Of Training On Sentence Processingsupporting
confidence: 74%
“…In some cases listeners may score highly on speech recognition tasks, but report that substantial "mental effort" was required to complete the task (Anderson Gosselin & Gagné, 2010). McCoy et al (2005) provided quantitative evidence of this effect, finding that for participants with mild-to-moderate hearing loss the increased perceptual effort required to decipher words produced notable effects on recall performance. Hearing impairment (McCoy, et al, 2005), age (e.g., Larsby, Hallgren, Lyxell, & Arlinger, 2005), and listening environment all play a role in influencing the degree of perceived listening effort.…”
Section: Accepted To Journal Of Speech Language and Hearing Research (mentioning
confidence: 98%
“…McCoy et al (2005) provided quantitative evidence of this effect, finding that for participants with mild-to-moderate hearing loss the increased perceptual effort required to decipher words produced notable effects on recall performance. Hearing impairment (McCoy, et al, 2005), age (e.g., Larsby, Hallgren, Lyxell, & Arlinger, 2005), and listening environment all play a role in influencing the degree of perceived listening effort. We posit that the integrity of the speech signal is an additional component that may influence perceived effort.…”
Section: Accepted To Journal Of Speech Language and Hearing Research (mentioning
confidence: 98%
“…For example, studies on the cognitive impact of hearing loss in elders (e.g., McCoy et al, 2005; have suggested that even when the speech signal is correctly identified by listeners with a mild-to-moderate hearing loss, the perceptual and cognitive efforts required for successful word recognition may take a toll on processing resources that might otherwise be used for subsequent processing (e.g., for encoding the speech content into memory). Systematic research on the differential impact of perceptual and cognitive load in speech segmentation is only now emerging, and the consequences of such an approach seem to go far beyond the segmentation domain.…”
Section: General R R Discussionmentioning
confidence: 99%